Implementation of a model to estimate the number of surviving cancer cells during radiotherapy treatment. (LACCEI, 2024)
The objective of this research work was to implement the model to calculate the number of surviving cancer cells during radiotherapy treatment, for which the analysis of the interaction process of radiation with cancer cells was carried out, identifying the variables of entrance, the body or main part. As a result, information was obtained on the number of cancer cells day by day during the radiotherapy treatment. In conclusion, the implementation of the interaction model can help in treatment planning since we can have an approximation of the tumor volume knowing the number of surviving cancer cells.